Methodological strategies guide with songs to improve the speaking and listening skills in the english teaching learning process with seventh grade learners at Juan Manuel Lasso Elementary School, during the academic cycle 2012 – 2013, located in Tanicuchi parish, Cotopaxi province, Latacunga Canton. - Bastidas Crespo, Juana del Rocío (2014)
The reality of the speaking and listening skills at the basic cycle for students in the English language learning is not good enough since no methodological tools are used for motivating students. The purpose of this research is to implement the music as instructional strategy that encourages effective learning in Basic Education students; therefore it is proposed to develop a methodological guide based on the use of songs, which contributes to the development of linguistic communication. The application of this guide seeks to create an environment free of tension, so that students express their ideas and feelings freely and for many of them to listen to music and to participate in the dynamics will provide them an opportunity to relax and forget their fears. For this reason, it is considered that music plays an important role by allowing the expression of ideas and feelings. The methods and techniques used for the development of this research process were: The Historical Logical Analysis Synthesis; Inductive- Deductive; the practical contribution is based on the use of songs, an open educational resource and an indispensable tool to promote language learning in the English classes.